ANXIETY, DEPRESSION AND QUALITY OF LIFE OF INDIVIDUAL WITH HEMODIALYSIS THERAPY - Haswita Haswita (UPT Penerbitan Universitas Jember)
Background: Chronic Renal Failure patients on hemodialysis have risk factors for psychological disorders such as anxiety and depression. The cause of chronic renal failure is a stressful condition in hemodialysis treatment, including frequent visits and long waiting times in the dialysis unit, the patient must continue to connect to the hemodialysis machine during dialysis resulting in restrictions in independent life. The anxiety and depression experienced to contribute to a decline in the quality of life. Methods: This research is a correlation study with the cross-sectional quantitative approach, which was performed on twenty patients with hemodialysis at Bhakti Husada Hospital, with accidental sampling technique. The instruments used Hamilton Anxiety Rating Scale (HARS), Beck Depression Inventory (BDI) and Word Health Organization Quality of Life – BREF (WHOQOL-BREF) questionnaires. The bivariate analysis used by Pearson product-moment and multivariate using multiple linear regression. Results: The results of this research indicate that r-0.143 and p = 0.274> 0.05 means there is no effect of anxiety on quality of life while the correlation of depression on quality of life shows r-0.532 with p 0.008 <0.05 means there is an influence. Regression analysis results in p 0.055> 0.05, indicating that almost no effect of anxiety, depression on quality of life. And seen R = 0.538 and R2 = 0.289 (28.9%) conclusion the anxiety and depression are moderately correlated to the quality of life. Conclusion: Chronic Renal Failure Patients who have hemodialysis have an effect on the condition of both physical and psychic, and therapy Hemodialysis can improve the quality of life. Keywords: Anxiety, Depression, Quality of Life, Patient with Hemodialysis